Preparation and characterization of Nickel (II) phthalocyanine tetrasulfonic acid tetrasodium salt for organic solar cells / Muhamad Saipul bin Fakir - Fakir, Muhamad Saipul (2013)
Organic solar cells (OSCs) referred to as third-generation solar photovoltaics, after crystalline silicon and thin-film solar technologies. There are two categories of OSCs:large molecules (polymer-based) and small molecules (oligomer-based). Herein, however only small molecules are used due to its lower cost compared to polymeric materials. Nickel (II) phthalocyanine tetrasulfonic acid tetrasodium salt (NiTsPc) and tris(8-hydroxyquinolinato) aluminium (Alq3) are utilized as donor layer and acceptor layer, respectively. The main focus of this study is to modify the donor layer via a solvent treatment in order to enhance the ability of the charge carrier transport at the donor/acceptor interface hence leading to the improvement in the OSC performance.Initially, NiTsPc thin films are deposited on the cleaned glass substrate using spin-coating technique at constant rotation speed to produce 120nm film. Surface modification was done by immersing the NiTsPc films in the selected low solubility solvents of chloroform and toluene. Morphology of the solvent treated NiTsPc films has shown some different features compared to the untreated film, as viewed by Atomic Force Microscopy (AFM)images. The treated film forms a smaller granular structure as a result of the etching process by the solvent. Prior to the next stage of solvent treatment, the NiTsPc films are thermally treated at 140°C. Formation of nano fibers can be clearly observed in the Field Effect Scanning Electron Microscopy (FESEM) images, as a result of thermal treatment.Then the influence of immersion time at 0, 40, 80 and 120 minutes on the nanofibers diameter size was examined by observing the FESEM images, for the NiTsPc films being soaked in the selected solvent. The number of small nanofibers increases upon immersing the NiTsPc films, compared to the untreated film. Further measurement via absorption spectroscopy has shown NiTsPc films possess two distinct regions in the B-band and the Q-band. There is an increase approximately 30% in light absorption intensity upon the immersion time of 60 minutes, compared to the untreated film. Furthermore, the optical energy gaps in these B and Q bands are calculated using a Tauc plot, to be in the range of 2.70 to 2.85 eV and 1.43 to 1.50 eV, respectively. The drop of 5% in the fundamental energy gap has been obtained for the film being treated 60 minutes in chloroform. The drop in the NiTsPc energy gap can be explained in terms of defects formation (density of states of energy level) upon solvent treatment. The presence of these defects is further supported by the results obtained from the Raman spectra. The intensity ratio between the D and G peak (ID/IG) in the Raman spectra is deviated from unity, indicating the defects formation in NiTsPc molecule due to the solvent treatment. In the final part of this study,the acceptor layer of Alq3 is brought into contact with the treated NiTsPc donor layer, which then sandwiched between two electrodes of indium tin oxide (ITO) and aluminium.The current density-voltage (J-V) curves present that the double value of short-circuitcurrent density, Jsc has been obtained in the device consists of treated NiTsPc. This result confirms the enhanced charge carrier transport at donor/acceptor interface which agrees with PL quenching phenomena. Therefore, the performance of OSC can be improved to some extent via thin film surface modification by soaking in a suitable solvent at an optimum time.